Taqarrub in the perspective of sufi exegesis: a comparative study of haqāʾiq al-tafsīr by abū ʿabd al-raḥmān al-sulamī (d. 412 h) and laṭāʾif al-isyārāt by abū al-qāsim al-qushayrī (d. 465 h) - Faridah Fransiska; Ziyad Ulhaq; Ade Naelul Huda (At Turots: Jurnal Pendidikan Islam, 2025)
This research examines the concept of taqarrub (spiritual proximity to God) from the perspective of Sufi exegesis through a comparative study of two monumental works: Haqāʾiq al-Tafsīr by Abū ʿAbd al-Raḥmān al-Sulamī (d. 412 H) and Laṭāʾif al-Isyārāt by Abū al-Qāsim al-Qusyairī (d. 465 H). Both texts represent the esoteric and spiritual dimension of Qur’anic interpretation, yet they differ in methodological approach and historical context. Al-Sulamī’s work largely compiles fragmentary sayings of early Sufi masters, while al-Qusyairī offers a more systematic exegetical framework grounded in Ashʿarite theology and early Shādhilī practices.Employing a qualitative, library-based method with thematic exegesis (tafsīr mawdhūʿī), this study identifies and analyzes Qur’anic verses related to taqarrub as interpreted by both exegetes. The findings indicate that al-Sulamī emphasizes the experiential and symbolic dimensions of Sufi thought, whereas al-Qusyairī integrates mystical insights with a coherent theological structure, reflecting the intellectual debates of his era. Despite criticism regarding their subjectivity and lack of isnād, both works demonstrate that Sufi exegesis is deeply rooted in Islamic scholarly tradition.The study highlights that these interpretations remain relevant for contemporary Muslims seeking spiritual depth amidst modern rationalism and materialism. By comparing the two tafsirs, this research contributes to bridging the gap between textual-rational exegesis and esoteric-spiritual readings of the Qur’an. Furthermore, it underscores the enduring significance of Sufi hermeneutics in providing inner tranquility, ethical refinement, and a holistic understanding of divine revelation.